Anchor in the storm : a novel - Sundin, Sarah (Sundin, Sarah. Waves of freedom, 2016)
"Nothing slows Lillian Avery down -- not her personal challenges and certainly not America's entry into World War II. She finally has a chance to prove herself as a pharmacist in Boston. The demands of her new job energize her. But society boy Ensign Archer Vandenberg's attentions only annoy -- even if he is her brother's best friend. During the darkest days of the war, Arch's destroyer hunts German U-boats in vain as the submarines sink dozens of merchant ships along the East Coast. Still shaken by battles at sea, Arch notices his men also struggle with their nerves -- and with drowsiness. Could there be a link to the large prescriptions Lillian has been filling? As the danger rises on both land and sea, the two must work together to answer that question. But can Arch ever earn Lillian's trust and affection?" -- Back cover.